Pengaruh Promosi Kesehatan dengan Media Video dan Booklet terhadap Pengetahuan Siswa mengenai Perilaku Sedentari di MAN 1 Medan - Saragih, Amaliyah Nurmely Rahmah; Andayani, Lita Sri (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2022)
Background. Sedentary behavior is a severe problem in public health since it can increase all causes of death and the risk of non-communicable diseases. Adolescents are the highest population with sedentary behavior, exceptionally high school students. To prevent sedentary behaviour, learning through media such as videos and booklets is necessary to promote health. Objective. The objective is to analyze the influence of health promotion with video and booklet media on students’ knowledge regarding sedentary behavior at MAN 1 Medan. Method. Quasi-experiment that used a non-equivalent control group design. The number of samples consisted of 30 students divided into 15 students in each intervention group. Analysis used Wilcoxon Signed Rank Test. Results. The students’ average knowledge before (13.20) and after (17.33) with p=0.001 were given an intervention by video. Meanwhile, the students’ average knowledge before (12.93) and after (15.33) with p=0.002 were given an intervention by booklet. Conclusion. There is a difference in students’ knowledge regarding sedentary behavior after being given health promotion with video and booklet. Both video and booklet as a health promotion media affected increased students’ knowledge about sedentary behavior. However, after being given intervention with video, students had a higher knowledge average than booklet.